The Relationship between Innovative Leadership, Readiness of Professional Nurses and Success in Nursing Administration of a University Hospital, the Lower Northern Region - tatuy, warapong; Ruetrakul, Jirarat; Suntayakorn, Chanjar (NU Journal of Nursing and Health Sciences, 2023)
This descriptive research aimed to investigate relationship among the innovative leadership of professional nurses, the readiness of professional nurses and the successful nursing administration in the university hospital, the lower northern region. The participants consisted of 226 professional nurses providing services to patients in the university hospital, the lower northern region and had working experiences in the unit at least one year. Questionnaires were used for data collection, consisted of four questionnaires: 1) demographic data, 2) the innovative leadership of professional nurses, 3) the readiness of professional nurses, and 4) the successful nursing administration. Questionnaires were tested for validity and reliability. The content validity of the questionnaires were 0.89, 0.93, 0.90 respectively. The Cronbach’s Alpha reliability coefficients of the questionnaires were 0.98, 0.95, 0.97 respectively. Data were analyzed by descriptive statistics and Pearson’s product moment correlation. The research findings were as follows. 1) Professional nurses perceived the innovative leadership of the nurses at the high level. 2) Professional nurses perceived the readiness of the nurses at the high level. 3) Professional nurses perceived the successful nursing administration of the nurses at the high level. 4) The innovative leadership had a positively significant relationship with the successful nursing administration in the university hospital (p < 0.01). Finally, 5) The readiness of professional nurse had a positively significant relationship with the successful nursing administration in the university hospital (p < 0.01).